Impact of targeted interventions on success of high-risk engineering students: a focus on historically underrepresented students in STEM - Atindama, Emmanuel; Ramsdell, Michael; Wick, David P.; Mondal, Sumona; Athavale, Prashant (Frontiers in Education, 2025)
IntroductionThe study examines the impact of targeted educational interventions on the academic success and retention of engineering students identified as high-risk, with a focus on two student groups historically underrepresented in STEM: underrepresented minority (URM) and female students. These interventions included an alternative curriculum pathway, a co-calculus support course, and spatial visualization training. Building on our previous work, we evaluated the outcomes of interventions designed to improve retention and graduation rates among the most academically underprepared students from these groups, who were consequently categorized as high-risk.MethodologyWe analyzed data from 10 student cohorts, covering 5 years before and 5 years after the interventions were implemented. We utilized a two-population proportion test to compare the groups' retention rates, graduation rates, and success in early STEM courses during pre- and post-intervention periods. Additionally, we constructed logistic regression models to identify key factors influencing on-time graduation.ResultsOur results show that the interventions significantly increased both the 4- and 6-year graduation rates for high-risk URM students by nearly 20 percentage points. Although high-risk female students improved retention and graduation rates, these changes were not found to be statistically significant. However, their performance in early foundation STEM courses, particularly Physics I and Calculus I, significantly improved post-intervention.DiscussionLogistic regression models indicated a shift in the significance of the graduation rate predictors post-intervention, demonstrating the efficacy of these tailored strategies. The reduced importance of Physics I grades in predicting on-time graduation during the intervention years suggests a benefit of the alternative curriculum pathway, which decoupled this course from Calculus I for high-risk students. Additionally, the intervention mitigated the previously significant predictor of being non-URM for on-time graduation, indicating a leveling effect for URM students. These findings highlight the potential of customized interventions to enhance the academic outcomes and retention of high-risk students in STEM disciplines.